2019
DOI: 10.1037/xge0000494
|View full text |Cite
|
Sign up to set email alerts
|

Parafoveal previews and lexical frequency in natural reading: Evidence from eye movements and fixation-related potentials.

Abstract: Participants’ eye movements and electroencephalogram (EEG) signal were recorded as they read sentences displayed according to the gaze-contingent boundary paradigm. Two target words in each sentence were manipulated for lexical frequency (high vs. low frequency) and parafoveal preview of each target word (identical vs. string of random letters vs. string of Xs). Eye movement data revealed visual parafoveal-on-foveal (PoF) effects, as well as foveal visual and orthographic preview effects and word frequency eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
84
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(108 citation statements)
references
References 111 publications
(218 reference statements)
17
84
2
Order By: Relevance
“…Fairly consistent results have been observed between EM and FRP measures for PoF effects of parafoveal preview [106,109,120], preview effects of predictability [26,108,113], frequency [113,117,120], and type of preview [110,114,117,120], foveal effects of text type [111], inter-letter spacing [118], repetition [107,110,112], word predictability [26,104,108,113], syntactic and semantic violations [116,119] and foveal load [114]. However, inconsistencies in EM and FRP results have been observed for PoF effects of semantic relatedness [106,[108][109][110]115], preview effects of semantic relatedness [110,115], foveal effects of semantic relatedness [108,110,115] and word frequency [113,120]. It remains the case, though, that co-registration investigations of aspects of reading are in their formative stages (with some effects being investigated in single studies only) and a greater body of experimental data is a necessity before firm conclusions may be formed as to the kinds of experimental manipulations that regularly and consistently produce FRP effects of specific kinds.…”
Section: Investigatedsupporting
confidence: 65%
See 3 more Smart Citations
“…Fairly consistent results have been observed between EM and FRP measures for PoF effects of parafoveal preview [106,109,120], preview effects of predictability [26,108,113], frequency [113,117,120], and type of preview [110,114,117,120], foveal effects of text type [111], inter-letter spacing [118], repetition [107,110,112], word predictability [26,104,108,113], syntactic and semantic violations [116,119] and foveal load [114]. However, inconsistencies in EM and FRP results have been observed for PoF effects of semantic relatedness [106,[108][109][110]115], preview effects of semantic relatedness [110,115], foveal effects of semantic relatedness [108,110,115] and word frequency [113,120]. It remains the case, though, that co-registration investigations of aspects of reading are in their formative stages (with some effects being investigated in single studies only) and a greater body of experimental data is a necessity before firm conclusions may be formed as to the kinds of experimental manipulations that regularly and consistently produce FRP effects of specific kinds.…”
Section: Investigatedsupporting
confidence: 65%
“…The second neural correlate of identity preview benefit is observed between 360-400 ms, when valid previews elicit more positive amplitudes than invalid previews over central sites of the scalp [102,110,115], and between 300-500 ms, when valid previews elicit more negative amplitudes than invalid previews over occipital areas of the scalp [121]. This late preview effect on the N400 component was not observed in Degno et al [120], indicating that this might be related to naturalness of the reading task or to baseline choices. The eye movement results also mapped onto the FRP data.…”
Section: Investigatedmentioning
confidence: 69%
See 2 more Smart Citations
“…First, although most effects obtained with the masked priming paradigm have been extended to a sentence reading using, for instance, Rayner's (1975) boundary, it is important to examine in future research the role of diacritics in a standard reading scenario (e.g., see Johnson, Perea, & Rayner, 2007, for evidence of transposed-letter similarity effects during reading; see also Marcet & Perea, 2018b, for evidence of visual similarity effects during reading). In a ideal scenario, this could be combined with a co-registration of the fixation-related potentials (see Degno et al, 2019). Second, Spanish orthography only contains one consonant letter with a diacritical sign (i.e.,ñ), and this may limit the generality of the findings.…”
Section: Discussionmentioning
confidence: 99%